Der konversationsanalytische Zugang zur Pflege. - Schönefeld, Daniel (Pflege & Gesellschaft, 2021)
The spoken word is not merely a fleeting phenomenon, but rather important material of which nursing is comprised and performed. Conversation analysis introduces a formal approach to the process of language construction and provides a further insight into the social order of nursing. Through conversation analysis, nursing can be considered a social practice in itself, continually organizing and reproducing itself, independent of individual motivations to act. This paper introduces conversation analysis - which in German nursing research is relatively uncommon - as an analytical approach to nursing science and illustrates the analytical process using an example. In particular, it shows how conversation analysis can contribute to the development of theory in this scientific field by enabling the network-like formation and synthesis of microtheories.